A Randomized Double-Blind, Cross-Over Trial of very Low-Calorie Diet in Overweight Migraine Patients: A Possible Role for Ketones? - Di Lorenzo, Cherubino; Pinto, Alessandro; Ienca, Roberta; Coppola, Gianluca; Sirianni, Giulio; Di Lorenzo, Giorgio; Parisi, Vincenzo; Serrao, Mariano; Spagnoli, Alessandra; Vestri, Annarita; Schoenen, Jean; Donini, Lorenzo M; et al. (Nutrients, 2019)
Here we aimed at determining the therapeutic effect of a very low-calorie diet in overweight episodic migraine patients during a weight-loss intervention in which subjects alternated randomly between a very low-calorie ketogenic diet (VLCKD) and a very low-calorie non-ketogenic diet (VLCnKD) each for one month. In a nutritional program, 35 overweight obese migraine sufferers were allocated blindly to 1-month successive VLCKD or VLCnKD in random order (VLCKD-VLCnKD or VLCnKD-VLCD). The primary outcome measure was the reduction of migraine days each month compared to a 1-month pre-diet baseline. Secondary outcome measures were 50% responder rate for migraine days, reduction of monthly migraine attacks, abortive drug intake and body mass index (BMI) change. Only data from the intention-to-treat cohort (n = 35) will be presented. Patients who dropped out (n = 6) were considered as treatment failures. Regarding the primary outcome, during the VLCKD patients experienced −3.73 (95% CI: −5.31, −2.15) migraine days respect to VLCnKD (p < 0.0001). The 50% responder rate for migraine days was 74.28% (26/35 patients) during the VLCKD period, but only 8.57% (3/35 patients) during VLCnKD. Migraine attacks decreased by −3.02 (95% CI: −4.15, −1.88) during VLCKD respect to VLCnKD (p < 0.00001). There were no differences in the change of acute anti-migraine drug consumption (p = 0.112) and BMI (p = 0.354) between the 2 diets. A VLCKD has a preventive effect in overweight episodic migraine patients that appears within 1 month, suggesting that ketogenesis may be a useful therapeutic strategy for migraines.